FORMING A SUSTAINABLE BUSINESS MODEL FOR CONSTRUCTION COMPANIES: ENERGY EFFICIENCY, CIRCULARITY AND DIGITAL TECHNOLOGIES - Галюк, Ірина; Єжак, Франко Франкович (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2025)
The article examines the transformation of the business model of construction companies in the context of modern energy, environmental and technological challenges. The emphasis is on the need to move from the traditional linear model of ‘design-build-deliver’ to an integrated, circular model of value creation that covers the entire life cycle of a building. Key global and national trends are analysed, in particular the growth of the construction sector's share in global energy consumption and CO₂ emissions, as well as the challenges of rebuilding Ukraine, which highlight the need for energy-efficient and low-carbon solutions. The critical role of digital technologies - BIM, LCM systems, IoT monitoring, smart building systems - in reducing embedded and operational emissions, optimising processes, improving the accuracy of design decisions and the efficiency of resource use is identified. In summary, the application of circular economy principles and the use of environmentally friendly or recycled materials is shaping a new value architecture in the construction business, providing long-term economic benefits, reducing environmental impact and increasing business sustainability. It has been shown that an integrated business model should include a combination of construction, energy efficiency, digital services, facility management, ESG-oriented management, and flexible modernisation processes throughout the entire life cycle. It has been proven that such a model can provide construction companies with competitive advantages in the context of tightening regulatory requirements, EU climate policy, higher sustainability standards and consumer demands. Prospects for further research are related to the development of quantitative models for evaluating the effectiveness of sustainable business models, refining indicators for measuring the low-carbon and circular potential of construction companies, and comparative analysis of ESG practices at different stages of the life cycle of objects. In general, it has been established that the transition to an integrated business model is not only an environmental necessity but also a strategic condition for increasing the competitiveness of Ukraine's construction sector in the long term.